A multidisciplinary investigation of the Barösund Shear Zone area, southern Finland - Vehkamäki, Teemu (My University, 2019)
The Barösund shear zone (BSZ) is a roughly 35 kilometres long and circa 500 m wide shear zone located within the Ekenäs archipelago, southern Finland. BSZ has an overall E-W trend but turns into N-S oriented in the middle part of the study area. The aim of this study is to find out whether BSZ forms a boundary between two distinct geological areas, terranes. For this purpose, geochronological, kinematic and geochemical research was carried out within and adjacent to BSZ. With these methods, the aim is to deduce the age of shearing, its kinematics and the geochemical characteristics of the adjacent intrusive rocks on both sides of BSZ. Three samples were collected for age determinations: the first sample was taken from an openly folded granitic dyke which cuts the sheared rocks. This was done to establish the minimum age of the shearing. Two further samples from a tonalite and a porfyric granite were taken south of BSZ. These samples were collected to improve the constraints of the general age of the intrusive rocks in the area. Age determinations were carried out with U-Pb method using separated zircons. The granite dyke is 1794±23 Ma old. This is similar to the results of the other workers and establishes the minimum age for the bulk of the deformation. The regional 1815–1830 Ma metamorphism can be regarded as the maximum age of the sample due to presence of sillimanite characteristic for the Svecofennian late orogenic metamorphism. The porfyric granite is 1889±10 Ma and the tonalite is 1877±11 Ma old. This makes them coeval of the early Svecofennian orogeny, the Fennian orogeny. Neither of the samples show signs of the late Svecofennian metamorphic overprint. Geochemically, intrusive rocks adjacent to BSZ both to North and South are volcanic arc rocks with subduction a component. This makes them typical 1.89–1.87 Ga Fennian orogenic intrusive rocks. Further North of BSZ, intrusive rocks change to late-orogenic crustal melt products. The kinematics of BSZ show both normal and reverse dip-slip movements. Since bulk of the thin sections used in studying the kinematics were taken from the middle part of the shear zone, normal component can be explained a with local zone of transtension. Reverse kinematics might be influenced by the nearby Jyly shear zone. Based on the results, the only factor pointing towards BSZ being a terrane boundary is the lack of late metamorphic overprint in the intrusive rocks south of BSZ.

Barösundin hiertovyöhyke on Tammisaaren saaristossa sijaitseva, noin 35 kilometriä pitkä ja 500 metriä leveä itä-länsi-suuntainen hiertovyöhyke, joka kääntyy tutkimusalueen keskellä pohjois-etelä -suuntaiseksi. Tässä tutkimuksessa on tarkoitus selvittää, onko BSZ kahden suuremman geologisen yksikön, eli terraanin raja. Tämän selvittämiseksi hiertovyöhykkeen alueella ja sen läheisyydessä suoritettiin geokronologisia, kinemaattisia ja geokemiallisia tutkimuksia. Näiden menetelmien avulla on tarkoitus selvittää hiertovyöhykkeen ikä, tapahtuneen hierron liikesuunta ja hiertovyöhykettä ympäröivien plutonisten kivien geokemialliset piirteet. Ikämäärityksiä varten kerättiin kolme näytettä. Ensimmäinen näyte otettiin hiertovyöhykettä leikkaavasta, avoimesti poimuttuneesta graniittisesta juonesta, tarkoituksena määrittää täten hierron minimi-ikä. Kaksi muuta näytettä kerättiin hiertovyöhykkeen eteläpuolelta tonaliitista ja porfyyrisestä graniitista. Näiden näytteiden tarkoituksena oli selvittää intruusioiden kiteytymisen ikä. Ikämääritykset toteutettiin U-Pb-menetelmällä käsinäytteistä erotetuista zirkoneista. Graniittinen juoni on iältään 1794±23 Ma. Tämä sopii yhteen aiempien tuloksien kanssa ja antaa minimi-iän, jota ennen pääosa hiertovyöhykkeen deformaatiosta oli tapahtunut. Maksimi-ikänä voidaan pitää 1830–1815 Ma alueellista metamorfoosia johtuen hiertyneiden kivien sisältämästä sillimaniitista, joka on tyypillistä Svekofenniselle myöhäisorogeeniselle metamorfoosille. Porfyyrisen graniitin ja tonaliitin iäksi saatiin 1889±10 Ma ja 1877±11 Ma. Tämä tekee niistä Svekofennisen orogenian alkuvaiheen, Fennian orogenian aikaisia. Kumpikaan näyte ei sisällä myöhäisorogeenisen metamorfoosin ikäisiä zirkoneja. Geokemiallisesti plutoniset kivet hiertovyöhykkeen välittömässä läheisyydessä sen etelä- ja pohjoispuolella ovat vulkaanisen kaarityypin kiviä, joissa on havaittavissa subduktiokomponentti. Tämä tekee niistä tyypillisiä, noin 1.89–1.87 Ga Fennian orogenian vaiheen kiviä. Pohjoisempana hiertovyöhykkeestä syväkivet muuttuvat myöhäisorogeenisiksi kuoren sulamistuotteiksi. Hiertovyöhykkeen kinematiikka osoittaa sekä normaali- että reverssisuunnan siirtymää. Koska valtaosa kinematiikan tutkimiseen tarkoitetuista ohuthieistä on kerätty hiertovyöhykkeen keskeltä, on normaalisiirtymä selitettävissä paikallisella transtensiolla, kun taas reverssisiirtymä saattaa johtua läheisen Jylyn hiertovyöhykkeen vaikutuksesta. Tutkimusten perusteella ainoa mahdollinen terraanirajaan viittaava tekijä on myöhäisorogeenisen metamorfoosin puute Barösundin hiertovyöhykkeen eteläpuolen plutonisten kivien ikämäärityksissä.
Keywords: Shear zones, Svecofennian orogeny, Geochronology, Geochemistry, Kinematics